(untitled) (AYUSHDHARA, 2025)
Mahasetu Rasa, a classical Kupipakwa Rasayana preparation described in Rasa Kamdhenu, requires systematic purification (Shodhana) of Parada, Vanga, and Gandhaka, followed by Kajjali formation and heating in an Electric Muffle Furnace. The present study aimed to standardize its pharmaceutical preparation and evaluate the final product using modern analytical techniques. Pharmaceutical observations confirmed the successful detoxification of raw materials. Materials and Methods: Raw materials were purified by traditional methods: Parada with Churnodaka and garlic paste, Vanga via Samanya and Vishesh Shodhana in various media, and Gandhaka by repeated Dhalana with ghee and cow’s milk. Kajjali was prepared by amalgamation and trituration, and Mahasetu Rasa was heated upto 550°C in EMF. Results: Purified materials exhibited expected detoxification and physical changes. Kajjali showed classical properties. Pharmaceutical observations confirmed the successful detoxification of raw materials, yield was after Shodhana, Shuddha Vanga (Sn) - 90.8%, Shuddha Gandhaka (S) - 88.08%, Shuddha Parada (Hg) - 88.40%, Kajjali - 98.66%, Kupipakwa yielded MSR1 - 38.5%, MSR2 - 40.06, MSR3 - 39.1% final product after 26 hrs of heating and completion. Conclusion: The standardized method ensures reproducible preparation of Mahasetu Rasa through effective purification, controlled sublimation and fixation using EMF heating, thereby producing a safe and uniform product suitable for both clinical and research applications.